3.9k views
2 votes
What is the solution to the equation below? -2 + √3x-2-6 O A. x = 22 62 OB. X 62 C. X= 6 O D. X= X = 10 3

User Kmn
by
5.4k points

1 Answer

7 votes

Starting with the given equation:


-2+\sqrt[]{3x-2}=6

Add 2 to both sides of the equation:


\begin{gathered} \Rightarrow-2+\sqrt[]{3x-2}+2=6+2 \\ \Rightarrow\sqrt[]{3x-2}=8 \end{gathered}

Square both sides of the equation:


\begin{gathered} \Rightarrow(\sqrt[]{3x-2})^2=8^2 \\ \Rightarrow3x-2=64 \end{gathered}

Add 2 to both sides of the equation:


\begin{gathered} \Rightarrow3x-2+2=64+2 \\ \Rightarrow3x=66 \end{gathered}

Divide both sides by 3:


\begin{gathered} \Rightarrow x=(66)/(3) \\ \Rightarrow x=22 \end{gathered}

Therefore, the solution to the given equation is:

User Francadaval
by
5.2k points